IMPLEMENTATION OF COMPETENCY STANDARDS ON VALUE OSCIE (OBJECTIVE STRUCTURED COMPETENT IN ISLAMIC VALUES EXAMINATION) OF MEDICAL STUDENTS IN THE UNIVERSITY OF MUHAMMADIYAH PURWOKERTO - Titik Kusumawinakhyu (International Islamic Medicine Forum, 2021)
The Competency Standards of Muhammadiyah Doctor were issued by Muhammadiyah Medical and Health Education Association (Asosiasi Pendidikan Kedokteran dan Kesehatan Muhammadiyah/APKKM). Muhammadiyah carries out the mission of da'wah to create all graduates in practicing amar ma'ruf nahi munkar . Integrated competencies require an evaluation at final examinition through a comprehensive test including attitudes, knowledge, and skills. This research was a descriptive method to describe the characteristics of the variables. This study aimed to determine the implementation of competency of Muhammadiyah’s doctor through the scores on the Islamic Doctor Muhammadiyah competency test with the OSCIE format for students at the professional stage. The research was conducted after the OSCIE exam held in December 2019 at the Faculty of Medicine, Muhammadiyah University of Purwokerto. The subjects were the final year students of the Medical Professional Education of Medicine Faculty who took OSCIE. The sample used is a total sampling of 46 professional students of the Faculty of Medicine, Muhammadiyah University of Purwokerto. The examination assessment consists of 4 stages; stage 1 prayer memorization, stage 2 selected surah memorization, stage 3 test of funeral prayer skills, stage 4 reading, and writing skills test of the Qur'an. The research results show that 46 students conducting OSCIE were 20 (43.47 %) male and 26 (5.52%) female. The range of values ​​in 70- <80 was obtained for stages 1, 2, 3, and 4, respectively: 30%, 24%, 30%, and 16%. The values ​​ranged from 80 to 99 at stages 1,2,3 and 4: 15%, 20%, 21% and 44%. The percentage of 100 values ​​at each stage 1,2,3 and 4 shows 50%, 30%, 10%, 10%.